Avaliação da qualidade, fertilidade e proteômica de ovos de casca vítrea de reprodutoras pesadas - Mendonça, Guilherme Arantes (2020)
The objective was to evaluate the influence of the eggshell type (normal and vitreous) on the parameters of fertility, internal and external quality of eggs, in addition to the proteomics of eggshell structures of broiler breeders. To evaluate the egg quality parameters, the experiment was divided into two phases. In experiment 1, 240 eggs (120 of normal shell and 120 of vitreous shell) were evaluated, within a maximum of 24 hours after laying, collected equally between four lots of Ross broilers, two lines (male and female) and two ages (38 and 46 weeks). In experiment 2, five trays of 162 eggs with normal eggshell and the same amount for vitreous eggshell were used, from a lot of grandparents of the male line of the Cobb genetics, at 40 weeks of age. For the proteomic analysis, eggs from four lots of broiler grandparents (same lots from experiment 1 of quality) were used, with 80 eggs selected, 20 from each lot (pool of 10 eggs with normal shell and 10 eggs with vitreous shell) by the external characteristic of the shell. Fragments of the shell structure (shells and shells membranes) were collected from each lot, manually crushed, homogenized and then selected 1 g from each pool to form the final analysis. Normal shell eggs showed higher averages than vitreous shell eggs for the variables Albumin Percent, Yolk Index, Albumin Index and Haugh units, and lower average for Magnesium Percent in the shell. The loss of humidity in the incubation was higher for eggs with vitreous shell, compared with eggs with normal shell. By proteomics, 309 different proteins (2989 peptides) were identified in the 8 samples evaluated from the shell structures. After statistical analysis comparing all lots and proteins, a difference was identified only for two proteins (ATPase- A0A1Y4CB63 and OVA fragments identical to Ovoalbumin- A0A2H4Y8Q2), and the differences between the proportions were significantly higher for vitreous shell. Among the proteins found, we highlight: Ovotransferrin, Ovalbumin, OVA protein fragments, Protein Y related to Ovoalbumin, Serotransferrin, Ovomucoid, 2-c-methyl glycerol 4-phosphate cytidylytransferase, SERPIN, Uncharacterized Protein (Ovostatin Gene), Aplha-1 -acid glycoprotein, ATPase and Uncharacterized Protein (Gene B5G11_16010). Vitreous shell eggs have a lower internal quality than normal shell eggs, in addition to losing more humidity during incubation (probably due to changes in the organic / protein matter in the shell). From the proteomic findings it is possible to speculate some alteration of gene expression in the uterus, which can lead to protein overexpression (for example OVA / Ovoalbumin protein), with an increase in the organic content of the matrix, and breakdowns in the biomineralized layers of vitreous shell eggs. Therefore, we suggest new researches of molecular profile between the different structures of the two types of shell, in addition to studies of different field and hatchery managements for vitreous shell eggs.